Conventional and natural compounds for the treatment of dermatophytosis - Lopes, Ana I. (2019)
Dermatophytes are a group of pathogenic fungi that exclusively infect the stratum corneum of the skin, nails, and hair, causing dermatophytosis. Superficial skin infections caused by dermatophytes have increased in the last decades. There are conventional antifungals that treat these infections, such as terbinafine, fluconazole, and others. However, the limitations of these treatments (resistance, side effects and toxicity) along with the increasing over-prescription, the misuse of these antifungals and the high treatment costs led to the search for new, alternative, natural-based antifungal drugs. These have multiple mechanisms of action, which works to their advantage, making it difficult for a fungus to create resistance mechanisms against all of them at the same time. The main objective of this work is to provide a state-of-the-art review on dermatophytes, dermatophytosis, and the existing treatments, both conventional and natural, such as chitosan and essential oils.